Characterization of carotenoid biosynthesis in newly isolated Deinococcus sp. AJ005 and investigation of the effects of environmental conditions on cell growth and carotenoid biosynthesis - Choi, Jun Young; Lee, Kunjoong; Lee, Pyung Cheon (Marine Drugs, 2019)
Our purpose was to characterize the structures of deinoxanthin from Deinococcus sp. AJ005. The latter is a novel reddish strain and was found to synthesize two main acyclic carotenoids: deinoxanthin and its derivative. The derivative (2-keto-deinoxanthin) contains a 2-keto functional group instead of a 2-hydroxyl group on a β-ionone ring. A deinoxanthin biosynthesis pathway of Deinococcus sp. AJ005 involving eight putative enzymes was proposed according to genome annotation analysis and chemical identification of deinoxanthin. Optimal culture pH and temperature for Deinococcus sp. AJ005 growth were pH 7.4 and 20 ◦C. Sucrose as a carbon source significantly enhanced the cell growth in comparison with glucose, glycerol, maltose, lactose, and galactose. When batch fermentation was performed in a bioreactor containing 40g/L sucrose, total carotenoid production was 650% higher than that in a medium without sucrose supplementation. The culture conditions found in this study should provide the basis for the development of fermentation strategies for the production of deinoxanthin and of its derivative by means of Deinococcus sp. AJ005.
Keywords: Bacterial Proteins; Bacteriological Techniques; Carotenoids; Cell Proliferation; Culture Media; Deinococcus; Fermentation; Gene Expression Regulation, Bacterial; Gene Expression Regulation, Enzymologic; Hydrogen-Ion Concentration; Temperature; Carotenoid; Deinococcus; Deinoxanthin